DIGITAL TRANSFORMATION OF POLITICAL INFLUENCE: DYNAMICS OF MODERN PROPAGANDA - Bondar, Evgen (Public Management and Policy, 2025)
The relevance of the study is determined by the fact that the implementation of political influence in the digital age extends beyond the classical models of propaganda. A shift is observed towards multi-level, interactive, algorithmically mediated interaction, where digital platforms, artificial intelligence, big data analytics, and digital citizen behavior play a key role. The research aims to explore the digital transformation of political influence through the lens of contemporary propaganda dynamics. The paper shows a shift from classical models of ideological mobilization through centralized media to decentralized, algorithmically mediated forms of interaction defined by digital platforms, artificial intelligence, and big data analytics. The hybrid nature of modern propaganda is emphasized, as it combines traditional communication methods with new technologies, including micro-targeting, the use of bots, deepfakes, and algorithmic content filtering. Special attention is paid to the epistemological shift in the paradigm of political communication: from centralized and verbal to fragmented, multimodal, and emotionally manipulative. The article outlines the threats of algorithmic authoritarianism, information overload, and cognitive manipulation, which undermine democratic resilience and blur the boundaries between truth, propaganda, and disinformation. At the same time, the necessity of developing digital sovereignty and media literacy as key mechanisms to counter disinformation and protect democratic values in the digital age is emphasized. It is established that the transformation of communication forms caused by digitalization expands the ontological boundaries of political power, and political propaganda becomes the infrastructural core of the power mechanism. One of the most alarming consequences of the digital transformation of political influence is the increased vulnerability of democracy to manipulation and information attacks. Digital propaganda becomes not just a tool of influence but also a means of undermining the foundations of the democratic order. It not only changes the tools of politics but also changes its very anthropology, eroding fundamental concepts of leadership, participation, trust, and identity.